2019
DOI: 10.1002/ijc.32493
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise dose and type during breast cancer chemotherapy on longer‐term patient‐reported outcomes and health‐related fitness: A randomized controlled trial

Abstract: The Combined Aerobic and Resistance Exercise (CARE) Trial compared different types and doses of exercise performed during breast cancer chemotherapy. Here, we report the longer‐term follow‐up of patient‐reported outcomes, health‐related fitness and exercise behavior at 6, 12 and 24 months postintervention. A multicenter trial in Canada randomized 301 breast cancer patients initiating chemotherapy to thrice weekly, supervised exercise consisting of a standard dose of 25–30 min of aerobic exercise (STAN; n = 96)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 40 publications
2
72
0
Order By: Relevance
“…We found that few of the short-term positive effects of the higher-dose aerobic and combined exercise programs during chemotherapy [2] were maintained during follow-up [15]. Conversely, there were strong positive associations between exercise behavior during the follow-up period and longer-term physical fitness, psychosocial outcomes, and quality of life [15]. These data suggest that longer-term maintenance of exercise after chemotherapy is critical for the sustained benefits of exercise.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…We found that few of the short-term positive effects of the higher-dose aerobic and combined exercise programs during chemotherapy [2] were maintained during follow-up [15]. Conversely, there were strong positive associations between exercise behavior during the follow-up period and longer-term physical fitness, psychosocial outcomes, and quality of life [15]. These data suggest that longer-term maintenance of exercise after chemotherapy is critical for the sustained benefits of exercise.…”
Section: Introductionmentioning
confidence: 72%
“…Flow of participants during the follow-up phase of the CARE Trial has been reported elsewhere [15]. Briefly, of the 301 randomized participants, 264 (88%) provided complete data at all three follow-up timepoints.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this trial, we compared the feasibility and bene ts of a home-based PA program during or after speci c cancer treatment to provide recommendations for patients undergoing breast cancer treatment. This AP program combined aerobic and resistance exercises, as proposed for the majority of trials for cancer patients (33). We did not compare the VO 2 values with a control group without AP because it would not have been ethical to perform breast cancer adjuvant treatment without proposing an APA program, even if the modality is not precise.…”
Section: Discussionmentioning
confidence: 99%